Um estudo inicial do uso de HQs na aula de matemática - SOUSA, Davison Renan Abreu de (2023)
In this work we will present three proposals for the use of comics (comics) involving mathematics, as we found several studies indicating that this resource is involved in a significant amount of elements that help in learning and made us conceive as a central objective to build material for teacher training in mathematics involving this feature. The material produced deals with the Numbering System, Combinatorial and Pythagorean Theorem contents and, transversally, an important part in the structuring of the comic book character, brings themes from the cultural context of Pará, respectively, legend of Curupira, Causo\Visagem and Crab Bragantino. The most underlying methodological construction in each proposal is to mathematically base the teaching action so that it promotes a class that makes the reading of comics by the students integrate into a teaching and learning process. In addition, we aim to involve teachers in a brief historical description of comics in society and their use as a didactic resource. For this, as a theoretical reference we used the works of VERGUEIRO (2004, 2013 and 2017), which discusses comics in the classroom and brings the pioneers in the study in Brazil, including academic research, as well as NETO (2013 and 2015), who addresses comics and educational practices, among others. And the methodology we used the most was based on the bibliographic study of comics as a didactic resource and the mathematics content of the proposals.